IMPLEMENTASI PERATURAN DIREKTUR JENDERAL IMIGRASI NOMOR IMI-1489.UM.08.05 TAHUN 2010 TENTANG PENANGANAN IMIGRAN ILEGAL (Studi di Kantor Imigrasi Kelas 1 Pekanbaru) - Adni, Dita Fisdian; Wardana, Data (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2017)
Since the last few years, the city of Pekanbaru be used as a storage area that is visited by many illegal immigrants who mostly come from the countries of the Middle East that is in conflict such as Iraq, Syria, Afghanistan, Iran and other countries. In its development, the increasing arrival and presence of illegal immigrants in the city of Pekanbaru has presented its own problems that feared will have an impact in the sector of ideology, political, economic, social, cultural, national security, immigration insecurity. While Immigration Office Class 1 Pekanbaru city itself is an institution that is given tasks and responsibilities within the Director General of Immigration regulation Number IMI-1489.UM.08.05 in 2010 on the handling illegal immigrants through its Head of Immigration Office to keeping an eye the illegal immigrants who were in the city of Pekanbaru and also for registration and periodic reporting of data for each month both qualitative and quantitative data are reported to the Director General of Immigration. Results from this study is the Director General of Immigration Regulation Number IMI-1489.UM.08.05 in 2010 on the Handling Illegal Immigrants can be categorized enough implemented. This can be seen from almost all sub-indicators such as communication, resources, dispotition and bureaucratic structure can be found in the implementation of the Director General of Immigration Regulation Number IMI-1489.UM.08.05 in 2010 on the handling Illegal Immigrants, although there are still some shortcomings and weaknesses in the implementation of these regulations.